Legal regulation of AI-assisted academic writing: challenges, frameworks, and pathways - Gao, Runyang; Yu, Danghui; Gao, Biao; Hua, Heng; Hui, Zhaoyang; Gao, Jingquan; Yin, Cha (Frontiers in Artificial Intelligence, 2025)
IntroductionThe widespread application of artificial intelligence in academic writing has triggered a series of pressing legal challenges.MethodsThis study systematically examines critical issues, including copyright protection, academic integrity, and comparative research methods. We establishes a risk assessment matrix to quantitatively analyze various risks in AI-assisted academic writing from three dimensions: impact, probability, and mitigation cost, thereby identifying high-risk factors.ResultsThe findings reveal that AI-assisted writing challenges fundamental principles of traditional copyright law, with judicial practice tending to position AI as a creative tool while emphasizing human agency. Regarding academic integrity, new risks, such as “credibility illusion” and “implicit plagiarism,” have become prominent in AI-generated content, necessitating adaptive regulatory mechanisms. Research data protection and personal information security face dual challenges in data security that require technological and institutional innovations.DiscussionBased on these findings, we propose a three-dimensional regulatory framework of “transparency, accountability, technical support” and present systematic policy recommendations from institutional design, organizational structure, and international cooperation perspectives. The research results deepen understanding of legal attributes of AI creation, promote theoretical innovation in digital era copyright and academic ethics, and provide practical guidance for academic institutions in formulating AI usage policies.